A clinical case of traumatic patellar instability in a patient with previous surgery for lateral patellar instability - Stefan Mogos; Stefan Mateoiu (Journal of Orthopaedic Reports)
Purpose: Medial patellar instability is a medical condition where the patella loses its stability in the trochlear sulcus and thus is at risk of medial subluxation during active or passive extension and flexion of the knee. In this paper we present the diagnosis, treatment and follow up of a medial patellar instability case, along with discussions on its specificity. Materials and methods: Our case report presents a 21 year old woman who presented with medial patellar instability after a high energy trauma. The patient had a history of recurrent lateral patellar dislocation for which trochleoplasty and MPFL reconstruction was performed 18 months before. Lateral patellotibial ligament reconstruction was performed. Results: Patient autonomy was fully restored, during normal day to day activities and significantly improved in sport activities such as running or more exhausting physical labour. Conclusion: Medial patellar instability is usually encountered as a consequence to hypercorrection after lateral release procedures in the surgical treatment of lateral patellar instability. However, our patient underwent lateral retinacular lengthening in the prior surgical procedure, but no lateral release. After returning to the usual daily and sports activities, the patient suffered a high energy trauma which was responsible for the medial patellar instability.